Kajian Prospek dan Strategi Pengembangan Usaha Pengolahan Aloe Vera Pada PT Libe Bumi Abadi - I Nyoman Suisnaya; Musa Hubeis; Budi Purwanto (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2009)
Aloe vera has a compete nutrition which has function as natural antioxidant. The objectives of this study are (1) to know the business prospect in market aspect and raw material supply, (2) to evaluate financial feasibility, (3) to evaluate business management in the management aspect and production technology, (4) to average business development strategy of PT. Libe Bumi Abadi. The method of analysis used were (1) descriptive method which was used in collecting data of raw material, market prospect, financial statement, selling volume, income and cost, and strategic competitor; (2) feasibility investment method; (3) analysis of strengths, weaknesses, opportunities and threats (SWOT) and Internal-External (IE) matrix. The result of the study showed that the business processing of Aloe vera needed investment cost Rp. 687.750.000 and average of operational cost Rp.1.997.400.000 per year. It was a proper business because it resulted Net Present Value (NPV) Rp.383.606.492, Internal Rate Return (IRR) 34.39%, Pay Back Period (PBP) during 3.6 years, Benefit Cost Ratio (BCR) 1.558 (> 1) and Break Event Point (BEP) 30,385.41 or 42.20% from used production capacities. The sensitivity analysis showed that the investment was susceptible with the decreasing of selling price 5% but it was still defend in the increasing of raw material 5%. Based on the SWOT analysis, some alternative strategies that are SO, ST, WO and WT. The strategy which recommended to PT. Libe Bumi Abadi is WO strategy; they are (1) minimal benefit and production, (2) finding the new partnership as a the fund resource. The result of the analysis IE matrix showed PT. Libe Bumi Abadi in quadrant V, which is growth. It showed that it passed through horizontal integration or consolidation by defending of selling level and profit